2021
DOI: 10.1038/s41598-021-84984-2
|View full text |Cite
|
Sign up to set email alerts
|

Telomere attrition rates are associated with weather conditions and predict productive lifespan in dairy cattle

Abstract: Telomere length is predictive of adult health and survival across vertebrate species. However, we currently do not know whether such associations result from among-individual differences in telomere length determined genetically or by early-life environmental conditions, or from differences in the rate of telomere attrition over the course of life that might be affected by environmental conditions. Here, we measured relative leukocyte telomere length (RLTL) multiple times across the entire lifespan of dairy ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 70 publications
2
29
0
Order By: Relevance
“…However, both short and long early‐life TL tended to be weakly associated with the lowest mortality rates over the lifespan in that study (Pepke, Kvalnes, et al, 2022 ), suggesting disruptive selection on TL. Furthermore, some studies have showed that early‐life TL was a poor predictor of survival, which was instead predicted by changes in TL (Boonekamp et al, 2014 ; Seeker et al, 2021 ; Wood & Young, 2019 ), which we did not measure in this study.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…However, both short and long early‐life TL tended to be weakly associated with the lowest mortality rates over the lifespan in that study (Pepke, Kvalnes, et al, 2022 ), suggesting disruptive selection on TL. Furthermore, some studies have showed that early‐life TL was a poor predictor of survival, which was instead predicted by changes in TL (Boonekamp et al, 2014 ; Seeker et al, 2021 ; Wood & Young, 2019 ), which we did not measure in this study.…”
Section: Discussionmentioning
confidence: 75%
“…Similarly, TL decreased with higher temperatures experienced by common lizards (Dupoué et al, 2017), desert toad-headed agamas (Phrynocephalus przewalskii, Zhang et al, 2018), and dairy cattle (Bos taurus, Seeker et al, 2021), but not in Gouldian finches (Chloebia gouldiae, Fragueira et al, 2019). However, TL increased with higher temperature in Eastern mosquitofish (Gambusia holbrooki, Rollings et al, 2014), spotted snow skinks (Niveoscincus ocellatus, Fitzpatrick et al, 2019), and dark-eyed juncos (Graham et al, 2019) and there was no effect of temperature manipulation on TL in Atlantic salmon (Salmo salar, McLennan et al, 2018) or three-spined sticklebacks (Gasterosteus aculeatus, Kim et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that studies based on both laboratory and natural populations indicate that a significant proportion of an individual's telomere length can be explained by environmental variation, i.e. harsher or unpredictable environments are linked to shorter telomeres or faster telomere shortening rate (Watson et al 2015, McLennan et al 2016, Angelier et al 2018, Seeker et al 2021; meta‐analysed in Chatelain et al 2020). Telomeres seem to be particularly sensitive to environmental variation at early life stages, including prior to birth or hatching (Haussmann et al 2012, Noguera et al 2020, Stier et al 2020) or via maternal effects and parental life histories (Haussmann et al 2012, McLennan et al 2018).…”
Section: The Use Of Telomeres In Eco‐evolutionary Studiesmentioning
confidence: 99%
“…This is supported by a recent study which took repeated measurement of the relative leukocyte telomere length in a dairy herd. Higher rates of telomere attrition in individual cows was predictive of a shorter productive lifespan, suggesting a link between telomere loss and health [ 58 ].…”
Section: Discussionmentioning
confidence: 99%